DESIGN-DRIVEN PLACE BRANDING THROUGH ADAPTIVE REUSE IN MULTICULTURAL HERITAGE DISTRICTS - Daniel Pandu Mau; Freddy Hendrawan; Ramanda Dimas Surya Dinata (Jurnal Pariwisata Tawangmangu, 2026)
Adaptive reuse of heritage buildings has become increasingly important for supporting the sustainability of historic districts. However, studies integrating design intervention, spatial character, and district identity formation within the context of place branding remain limited, particularly in multicultural heritage districts. This study aimed to examine how design interventions in heritage buildings shaped spatial character, generated spatial experience potential, and contributed to district identity formation in the Old Town of Surabaya. This research employed a qualitative approach using a multiple-case study strategy involving four heritage buildings representing different cultural zones. Data were collected through field observation, visual documentation, and literature review, and subsequently were analyzed using a descriptive-interpretative approach through spatial configuration analysis, functional transformation analysis, and cross-case comparison. The findings indicated that design interventions influenced spatial configuration, circulation patterns, functional hierarchy, and contextual integration, resulting in diverse forms of spatial experience potential. The findings further indicated that spatial experience potential functioned as a mediating mechanism between spatial transformation and place perception, while place branding in heritage districts emerged through the interaction between spatial identity, narrative meaning, and spatial experience generated through design. This study developed a design-driven place branding model that linked design intervention, spatial experience potential, and district identity formation. Future research is recommended to further validate this model through post-occupancy evaluation and visitor perception studies across different heritage district contexts.